2011
DOI: 10.1128/iai.05799-11
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Naturally Occurring Interleukin-17A-Producing γδ T Cells in the Lung at the Early Stage of Systemic Candidiasis in Mice

Abstract: Interleukin-17A (IL-17A)-producing ␥␦ T cells differentiate in the fetal thymus and reside in the peripheral tissues, such as the lungs of naïve adult mice. We show here that naturally occurring ␥␦ T cells play a protective role in the lung at a very early stage after systemic infection with Candida albicans. Selective depletion of neutrophils by in vivo administration of anti-Ly6G monoclonal antibody (MAb) impaired fungal clearance more prominently in the lung than in the kidney 24 h after intravenous infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
73
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 53 publications
3
73
1
Order By: Relevance
“…However, we observed that TCR-d and TAP1 deficiency, but not MHCII deficiency, also affected early Brucella control in the lungs, suggesting that these cells could be a potential source of IL-17A in our model. In keeping with this observation, IL-17 production by g/d T cells was reported in a Brucella model (65) and in several other pulmonary infectious models (66)(67)(68).…”
Section: Discussionmentioning
confidence: 52%
“…However, we observed that TCR-d and TAP1 deficiency, but not MHCII deficiency, also affected early Brucella control in the lungs, suggesting that these cells could be a potential source of IL-17A in our model. In keeping with this observation, IL-17 production by g/d T cells was reported in a Brucella model (65) and in several other pulmonary infectious models (66)(67)(68).…”
Section: Discussionmentioning
confidence: 52%
“…γδ 17 cells are observed in lungs after systemic C. albicans infection, and both Il17 −/− and Tcrd −/− mice are defective in neutrophil recruitment and fungal clearance 84. Interleukin‐17 is produced in tongue‐resident γδ T cells as well as CD3 +  CD4 + CD44 hi  TCR‐ β +  CCR6 + natural Th17 cells within 1–2 days after oral C. albicans infection 85.…”
Section: γδ17 Cells In Pathogen Clearancementioning
confidence: 99%
“…Recently, it was found that IL-17A production by ␥␦ T cells rather than CD4 ϩ ␣␤ T cells plays an important role in the immune response to pulmonary Mycobacterium bovis Bacillus Calmette-Guérin (BCG) infection as well as in BCG-induced lung granuloma formation (13)(14)(15). We have also reported the importance of IL-17A-producing ␥␦ T cells in other models of infection of mice with Escherichia coli, Candia albicans, or BCG, which are involved in the neutrophil-mediated clearance of the pathogens or tumor cells (16)(17)(18). These findings suggest the hypothesis that a novel host defense mechanism mediated by the "innate" IL-17A-producing ␥␦ T cells is acting in innate immunity and initiating an inflammatory response following a microbe invasion.…”
mentioning
confidence: 97%